A performance improvement of Domosi’s cryptosystem - Khaleel, Ghassan; Turaev, Sherzod; Mohd Tamrin, Mohd Izzuddin; Alshaikhli, Imad Fakhri Taha (2015)
Dӧmӧsi’s cryptosystem [2, 3] is a new stream cipher based on finite automata. The cryptosystem uses specific deterministic finite accepters as secret keys for the encryption and decryption. Though this cryptosystem has been proven to be secure against different standard attacks (see [8]), the proposed encryption algorithms in [2, 3] involve exhaustive backtracking in order to generate ciphertexts. In this research, we propose a modified encryption algorithm to improve performance of the system up to a better linear-time without effecting its security.